2016
DOI: 10.1186/s12913-016-1739-1
|View full text |Cite
|
Sign up to set email alerts
|

Informing a Canadian paramedic profile: framing concepts, roles and crosscutting themes

Abstract: BackgroundParamedicine is a rapidly evolving health profession with increasing responsibilities and contributions to healthcare. This rapid growth has left the profession with unclear professional and clinical boundaries. Existing defining frameworks may no longer align with the practice of paramedicine or expectations of the public. The purpose of this study was to explore the roles paramedics in Canada are to embody and that align with or support the rapid and ongoing evolution of the profession.MethodsWe us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 43 publications
2
65
0
1
Order By: Relevance
“…Paramedics provide care in the field, en route to the hospital, and increasingly in community settings. Paramedics’ scope of practice varies by region and level of training 1 , 11 ; it includes both basic (eg, medication administration) and specialized (eg, intubation) interventions, as well as direct transport to facilities for suspected cardiovascular emergencies (eg, myocardial infarctions), among other skills and protocols. 1 Skillsets and structure of paramedic services vary both within and between countries and continue to develop.…”
Section: The Role Of Paramedics In Psychosocial Carementioning
confidence: 99%
See 2 more Smart Citations
“…Paramedics provide care in the field, en route to the hospital, and increasingly in community settings. Paramedics’ scope of practice varies by region and level of training 1 , 11 ; it includes both basic (eg, medication administration) and specialized (eg, intubation) interventions, as well as direct transport to facilities for suspected cardiovascular emergencies (eg, myocardial infarctions), among other skills and protocols. 1 Skillsets and structure of paramedic services vary both within and between countries and continue to develop.…”
Section: The Role Of Paramedics In Psychosocial Carementioning
confidence: 99%
“…This includes traditional response to acute emergencies, community health care and primary health care roles, as well as addressing more chronic health conditions, prevention, and education. 11 …”
Section: The Role Of Paramedics In Psychosocial Carementioning
confidence: 99%
See 1 more Smart Citation
“…The importance of communication cannot be over emphasised as alongside patient safety and compassion was found to be one of the crosscutting themes in all paramedic roles (Tavares, Bowles, & Donelon, 2016). However, in this study paramedic students reported challenges in communicating with people with dementia and understanding their needs.…”
Section: Challenges Of Communicating With People With Dementiamentioning
confidence: 62%
“…'Teamwork/diplomacy' is not defined in this study, however the term 'teamwork' emerges in other paramedic centred work, and is defined as the paramedic working in chain of patient care. The 'team members' include emergency room nurses, doctors and eventual outpatient services (Tavares, Bowles , & Donelon, 2016), most of whom a paramedic would have very little personal contact with. Post-traumatic stress is a current topic in the paramedic field.…”
Section: Paramedic Safety Studiesmentioning
confidence: 99%